Rutin (quercetin-3-rutinoside) modulates the hemostatic disturbances and redox imbalance induced by Bothrops jararaca snake venom in mice. - Ana Teresa Azevedo Sachetto; Jaqueline Gomes Rosa; Marcelo Larami Santoro (Public Library of Science (PLoS), 2018)
Snakebites are a major Collective Health problem worldwide. In Brazil, Bothrops jararaca snake venom (BjV) evokes hemostatic disturbances, bleeding manifestations, and redox status imbalance. Specific antivenom therapy, although efficacious to revert most snakebite-induced manifestations, is incapable of treating secondary manifestations, such as oxidative/nitrosative stress. Searching for new complementary therapies that could attenuate physiological derangements triggered by envenomation, we elected to test quercetin-3-rutinoside (rutin) by its potential as both a potent antioxidant and a hemostasis modulatory compound. The activity of rutin was evaluated both on the biological activities of crude BjV in vitro, and in vivo by the ability of rutin (14.4 mg/kg b.w.) to modulate hematological, hemostatic and redox status markers altered by BjV injection (1.6 mg/kg b.w., s.c.) in mice. In vitro, rutin failed to inhibit BjV-induced platelet aggregation and biological activities of major BjV enzymes (metalloproteinases, phospholipases A2, serine proteases, and L-amino acid oxidases). On the other hand, rutin attenuated local hemorrhage, and the increase in reactive species, prevented the fall in RBC counts and fibrinogen levels, diminished tail bleeding and shortened prothrombin time (PT) evoked by envenomation. Furthermore, rutin reduced tissue factor (TF) activity and altered the protein expression of TF in liver, lungs, heart and skin. In conclusion, the disturbances in redox status and hemostatic system induced by B. jararaca envenomation were modulated by rutin, suggesting it has a great potential to be used as an ancillary therapeutic agent for snakebites.